TRANSFORMATION OF WAVES SPREADING ALONG BURIED PIPELINE BECAUSE OF CONSTRUCTIVE INCLUSIONS - V V Lalin; G V Denisov (Structural Mechanics of Engineering Constructions and Buildings, 2013)
The paper considers the dynamic behavior of buried pipeline with constructive inclu- sion. It is shown that a traveling wave is transformed into transmitted and reflected waves. The effect of the analytical dependence is assessed. It is shown that the construc- tive inclusion reduces the level of dynamic impact.